Pengaruh Electronic Word Of Mouth (E-WOM) dan Social Media Marketing Activities terhadap Purchase Intention Dimediasi Brand Image - Nunung Sari; Ritta Setiyati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Social media marketing activities an important role in marketing strategies that can be implemented by e-commerce companies by providing the best service for consumers to improve the company's brand image and increase consumer purchase intention. The purpose of this study was to measure more specifically Social media marketing activities on brand image and purchase intention. This type of research is quantitative with a purposive sampling technique distributed through a questionnaire to 100 respondents who use the Tiktok Shop application, male and female, aged 18-55 years and intend to or have purchased skincare products through the Tiktok Shop application and are in the DKI Jakarta area. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study tested with the results that all affect. This study contributes to e-commerce companies for skincare products on Tiktok Shop in maintaining and increasing purchase intention, which can be seen from several factors, namely always having new innovations in every feature presented and presenting information that is appropriate and needed by consumers. Then e- commerce companies also need to listen to consumer criticism that can be constructive.